A Network Pharmacology-Based Strategy For Predicting Therapy Targets Of Beta-Sitosterol In Treating Diabetic Retinopathy - Sun, Kexin; Yu, Peiran (Journal of Ophthalmic Science, 2024)
Background Beta-Sitosterol (SIT) is an active TCM compound employed to treat diabetic retinopathy (DR). A network pharmacology approach to understanding the active ingredients and the therapeutic mechanisms underlying DR has not been pursued. Methods The potential targets for DM were identified according to the MedGene, Gendome, HGNC, OMIM, GeneCards, PheGenI, GEO, and STRING database. The herb and components were predicted and screened by network pharmacology through oral bioavailability and drug-likeness filtration using the Traditional Chinese Medicine Systems Pharmacology Analysis Platform database. A network pharmacology prediction and network analysis were used to predict the active potential targets and pathways of SIT application to DR. Results We found the Top 15 DR-related genes by screening in 9 databases. 26 kinds of TCM and nearly 300 kinds of active ingredients. SIT exists in 10 kinds of DR-treat TCM. The comprehensive network pharmacology approach was successful in identifying 23 kinds of core genes for SIT treating DR. ERBB3 and IGF2-related PI3K-Akt signaling pathway or EDN3, IGF2 and SPP1-related receptor ligand activity pathway might be the main pharmacological targets, and pathways in DR. We speculated that SIT was effective for the treatment of DR.  Conclusion Based on the network pharmacology, we predicted the potential targets of SIT in treating DR and helped to illustrate the mechanism of action. Our study identifies key genes and pathways associated with the prognosis and pathogenesis of DR from new insights.
Keywords: traditional Chinese medicine; network pharmacology; Beta-Sitosterol; diabetic retinopathy; bioinformatics analysis